Comparative Leaf Surface Anatomy of Woody Species of Tamaulipan Thornscrub, North-Eastern Mexico and its Possible Relation with Taxonomic Delimitation and Drought Resistance - Rodriguez, Humberto Gonzalez; Maiti, Ratikanta; Balboa, Perla Cecilia Rodriguez; Moncivaias, Jose Guadalupe Marmolejo; Kumari, Aruna (International Journal of Bio-resource and Stress Management, 2016)
A comparative study has been undertaken during May to July, 2016 in Forest Science Faculty Experimental Research Station, UANL, Mexico on the leaf surface anatomy of 30 native woody species of the Tamaulipan Thorn Forest and its utility in taxonomy and possible adaptation to the prevailing semiarid conditions. The results showed the presence of large variability in several leaf anatomical traits viz., waxy leaf surface, type of stomata, its size, and distribution. Some of the species possess special traits related to adaption in the environments such as waxy leaf surface, sunken stomata, the absence of stomata on the adaxial and or abaxial surface, thereby reducing loss in transpiration mentioned before. The presence of waxy leaf surface in most of the species such as Amyris texana, Celtis pallida, Guaiacum angustifolium, Acacia berlandieri, Karwinskia humboldtiana could help in the reflectance of solar radiation, thereby keeping leaf temperature cooler. The species have been classified on the basis of various traits which can be used in species delimitation and adaptation to the semiarid condition such as waxy leaf surface, absence or sparse stomata on the leaf surface, sunken stomata. The species identified as better adapters to semiarid environments on the basis of the presence and absence of stomata on both adaxial and abaxial surface such as: Berberis chochoco, Celtis laevigata, Condalia hookeri, Diospyros palmeri, Diospyros texana, Ebenopsis ebano, Ehretia anacua, Forestiera angustifolia, Havardia pallens, Helietta parvifolia, Karwinskia humboldtiana, Sargentia greggii, Sideroxylon celastrinum, Zanthoxylum fagara. Research is needed to confirm water relations and drought resistance of these selected species.